Pembangunan Synonym Set Kosa Kata Al-Quran dengan Pendekatan WordNet - Laras Gupitasari (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
Research using Quran in of computational linguistics is very interesting and useful from the importance of Quran for Muslims because it is holy book for them. Due to the current lack of language resources for Quran research, this research aims to build a synonym set of Quran that can be used as a prototype to build a Quranic Thesaurus. This study only uses nouns as a dataset, and approach using WordNet and English translations of the Quran. In grouping words to produce synonym sets, this study using the hierarchical clustering method. Finally, the evaluation of the results of the synset is done by the F-Measure method.